A Collective Micro Food Farming: Maximizing the Limited Space of Urban Neighborhood - Harani, Arnis Rochma; Azmi, Fathurrahman Nur; Prassetyo, Kelfin Ilyas; Au-Yong, Cheong Peng (UI Scholars Hub, 2025)
This paper examines the concept of urban farming in residential areas with limited space to provide food security while improving the environment. The practice of cultivating food crops, vegetables, fruits, or medicinal plants in small spaces such as yards, rooftops, balconies, walls, terraces, or indoor spaces is a form of domestic adaptation with significant ecological and social impacts in urban areas. This study is part of a community service program that aims to maximize limited space for food production and green space. Three phases of the activity methodology are involved in this program, including collecting spatial data to identify potential areas for urban farming, developing a design concept for a limited-land development that is based on food security, and conducting community workshops aimed at building awareness and collective participation in sustainable environmental management. The approach used in this program allows the community to actively participate in both design and implementation processes. The result of the activities showed how urban farming practices facilitate the development of community-based collective mechanisms, including the recycling of used objects as planting media and design elements. It provides a model for optimizing limited land that can be adapted to urban residential contexts. This urban farming model practice expands the discussion of participatory-based community engagement through collective mechanisms to formulate space-optimization strategies. Thus, urban farming on limited space is both a strategy for providing micronutrients and a spatial design strategy for enhancing environmental quality and social sustainability within densely populated urban areas.